2010
DOI: 10.1111/j.1462-2920.2009.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Transporter genes expressed by coastal bacterioplankton in response to dissolved organic carbon

Abstract: Coastal ocean bacterioplankton control the flow of dissolved organic carbon (DOC) from terrestrial and oceanic sources into the marine food web, and regulate the release of inorganic carbon to atmospheric and offshore reservoirs. While the fate of the chemically complex coastal DOC reservoir has long been recognized as a critical feature of the global carbon budget, it has been problematic to identify both the compounds that serve as major conduits for carbon flux and the roles of individual bacterioplankton t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
214
2
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 229 publications
(239 citation statements)
references
References 42 publications
19
214
2
4
Order By: Relevance
“…Although abundant in 16S rRNA amplicon libraries (assuming no major biases in PCR amplifications), this group appears to have low per-cell levels of gene expression and did not show a rapid transcriptional response (that is, within the 30 min incubation) to DMSP addition (Figure 4). This finding is consistent with previous marine metatranscrioptomic studies Poretsky et al, 2009Poretsky et al, , 2010 and suggests that SAR11 members may not exhibit substantial transcriptional responses to substrate supply, at least on short time Supplementary Table S2. The C or D at the end of the category names refers to the Control or DMSP libraries, respectively.…”
Section: Taxonomic Analysissupporting
confidence: 82%
See 2 more Smart Citations
“…Although abundant in 16S rRNA amplicon libraries (assuming no major biases in PCR amplifications), this group appears to have low per-cell levels of gene expression and did not show a rapid transcriptional response (that is, within the 30 min incubation) to DMSP addition (Figure 4). This finding is consistent with previous marine metatranscrioptomic studies Poretsky et al, 2009Poretsky et al, , 2010 and suggests that SAR11 members may not exhibit substantial transcriptional responses to substrate supply, at least on short time Supplementary Table S2. The C or D at the end of the category names refers to the Control or DMSP libraries, respectively.…”
Section: Taxonomic Analysissupporting
confidence: 82%
“…Sequences unidentified in RefSeq but with similarity to sequences in the GOS metagenome accounted for 9% of total reads (Supplementary Table S1). An average of 17% of sequences remained unidentified, possibly representing unknown genes, poorly conserved regions of known genes (Poretsky et al, 2010) or small RNAs with regulatory functions (Shi et al, 2009). In general, functional assignments of transcripts in control versus experimental treatments indicated that bacterioplankton activity was stimulated within 30 min of DMSP addition.…”
Section: Overall Patterns In Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no evidence in the metatranscriptome that heterotrophy had a significant role in the nutrition of this MG1C population. MG1C reads were not assigned to COGs for transporters of organic compounds (Supplementary Tables 3 and 4), in contrast to the high proportion of reads in the Bacteria metatranscriptome that were assigned to transporters (B20% of the Bacteria reads assigned to the top 50 COGs, Gifford unpublished data) or found previously in a Bacteria-dominated metatranscriptome retrieved from a near-by site (Poretsky et al, 2010). Also, the ratio of MG1C amoA genes to MG1C 16S rRNA genes in these samples was 0.51 ( Figure 1b).…”
Section: Ammonia Uptake and Oxidationmentioning
confidence: 78%
“…The advent of 16S rRNA sequencing and environmental genomics has revolutionized microbial ecology by identifying the genetic diversity (Rappé et al, 1997) and functional potential (DeLong et al, 2006) of a community without the need for cultivation. In particular, the comparative 'omics' strategy, relying on sequence comparisons to infer biogeochemical activity (Beja et al, 2001;Treusch et al, 2005;Poretsky et al, 2010), has been enormously fruitful in providing information about ecosystem function for entire microbial communities. Yet it is clear that although molecular surveys that describe the natural history of complex microbial systems can intimate which functions specific microorganisms or populations may perform, hypothesis-driven manipulative experiments are a critical follow-up step to enable quantitative associations between function and identity.…”
Section: Introductionmentioning
confidence: 99%